2021
DOI: 10.21608/jpp.2021.85866.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Distribution Patterns and Growth Regulators on Morphological, Yield and Technological Characters of Egyptian Cotton

Abstract: A field experiment was conducted at the Experimental Farm, Faculty of Agriculture, Menoufia University, Shebin El-Kom, Egypt during 2019 and 2020 seasons to study the effect of plant distribution patterns i.e. D1 (sowing cotton in furrows 70 cm width in one ridge with 25 cm between hills and two plants/hill), D2 (sowing cotton in furrows 70 cm width in one ridge with 12.5 cm between hills and one plant/hill), D3 (sowing cotton in beds 140 cm width in two ridges with 25 cm between hills and two plants/hill), D4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Walelgn (2020) reported that cotton fiber quality properties inclusive fiber length, micronaire reading and fiber strength were not influenced by the main effect of inter-and intra-row spacing. Ali et al (2021) indicated that fiber strength and length uniformity index were not significantly influenced by plant distribution systems. Altundag and Karademir (2021) found that the differences among planting spacings (5, 10, 15, 20 and 25 cm) were not statistically significant for fibre micronaire, fibre length (mm), fibre strength and fibre uniformity (%).…”
Section: Vi1 Effect Of Hill Spacingmentioning
confidence: 93%
See 2 more Smart Citations
“…Walelgn (2020) reported that cotton fiber quality properties inclusive fiber length, micronaire reading and fiber strength were not influenced by the main effect of inter-and intra-row spacing. Ali et al (2021) indicated that fiber strength and length uniformity index were not significantly influenced by plant distribution systems. Altundag and Karademir (2021) found that the differences among planting spacings (5, 10, 15, 20 and 25 cm) were not statistically significant for fibre micronaire, fibre length (mm), fibre strength and fibre uniformity (%).…”
Section: Vi1 Effect Of Hill Spacingmentioning
confidence: 93%
“…In this concern, increasing plant spacing resulted in a greater seed cotton yield/fed (El-Shazly, 2020). Ali et al (2021) indicated that boll weight and 100-seed weight were not significantly affected by plant distribution patterns. Hu et al (2023) used 3 planting densities (75,000; 90,000 and 105,000 plants ha −1 ).…”
Section: Yield and Its Contributory Characters Iii1 Effect Of Hill Sp...mentioning
confidence: 93%
See 1 more Smart Citation
“…Boll shedding is one of the main factors contributing to yield loss in cotton, a problem that the application of NAA can mitigate. Due to its function in cell division and elongation, this causes increased fruiting branches and bolls [ 20 ]. Additionally, it has been discovered that salicylic acid improves physiological and biochemical functions, leading to improved crop growth and production [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…NAA (Naphthalene acetic acid) can be applied to ameliorate the shedding effect of bolls which is one of the major causes for the yield loss. Its role in cell division and cell elongation paves the way in formation of more fruiting branches and bolls [9]. Salicylic acid (SA) also found to enhance various physiological and biochemical processes that results in better growth and productivity of the crop [10].…”
Section: Introductionmentioning
confidence: 99%